2015
DOI: 10.1007/s10616-015-9851-3
|View full text |Cite
|
Sign up to set email alerts
|

Agitation increases expansion of cord blood hematopoietic cells and promotes their differentiation into myeloid lineage

Abstract: Mechanical stress caused by agitation is one of the factors that can affect hematopoietic stem cell expansion in suspension bioreactors. Therefore, we have investigated the effects of agitation on umbilical cord blood hematopoietic stem cell (UCB-HSC) growth and differentiation. A comparison was made between various agitation rates (20, 40 and 60 rpm) in spinner-flask and cells cultured in glass petri dish as a static culture. Moreover, the fluid dynamic at various agitation rates of spinner-flask was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…However, also in this context the estimated effective wall shear stresses were around 0.5 Pa 69 . In vitro , effects of fluid dynamics on the expansion of mononuclear cells from UCB (containing HSPCs) in spinner flasks could be observed at shear stresses of ~0.1 Pa 70 . Therefore, it appeared that the shear stress occurring in the present study in the artificial bone marrow analog during perfusion was too small to effectively stimulate cells mechanically.…”
Section: Discussionmentioning
confidence: 99%
“…However, also in this context the estimated effective wall shear stresses were around 0.5 Pa 69 . In vitro , effects of fluid dynamics on the expansion of mononuclear cells from UCB (containing HSPCs) in spinner flasks could be observed at shear stresses of ~0.1 Pa 70 . Therefore, it appeared that the shear stress occurring in the present study in the artificial bone marrow analog during perfusion was too small to effectively stimulate cells mechanically.…”
Section: Discussionmentioning
confidence: 99%
“…Stirred tank, fixed-bed, agitated, and rotating-wall bioreactors have all been used for ex vivo HSPC expansion. Hosseinizand et al [35] used an agitation bioreactor operating at 40 rpm; total cell proliferation was maximal by day 14. However, engraftment capacity was not confirmed, and total cell fold expansion was disappointing ($5-fold) despite long-term incubation (14 days).…”
Section: Discussionmentioning
confidence: 99%
“…As microdroplets are formed in these systems, shear forces will change ( Xia et al, 2017 ; Zhan et al, 2022 ). Studies have shown that shear stresses within the hydrogel suspension could reduce the survival of HSCs ( Hosseinizand et al, 2016 ). Mahadik et al (2014) fabricated a microfluidic multicellular gradient hydrogel platform and observed that the viability of MSCs and HSCs was not significantly influenced by flow characteristics.…”
Section: Engineering Hydrogels Based On Niche Physiologymentioning
confidence: 99%